Influence of training on the response to exercise of adrenocorticotropin and growth hormone plasma concentrations in human swimmers - Bonifazi, M.; Bela, E.; Lupo, C.; Martelli, G.; Zhu, B.; Carli, G. (European Journal of Applied Physiology, 1998)
Aerobic training affected v4 (Laktat 4 mmol/l) levels, which were highest 18 weeks after the beginning of the season; at the same time, while [ACTH] response was attenuated, [GH] response was enhanced. These results could be considered as adaptations to the exercise intensity. In our training programme, these adaptations seemed to have occurred between the 12th and 18th weeks of the training season.